Fluorescence Study on the Interaction of Human-Like Collagen and Copper(II) - Yu, Y.Y.; Fan, D.D. (Asian Journal of Chemistry, 2011)
Fluorescence spectroscopy and UV-VIS absorption spectroscopy were employed to analyze the binding of Cu2+ to human-like collagen (HLC) with Cu2+ concentrations from 0 to 1.0 × 10-4 mol L-1 at 273 and 298 K. The fluorescence titration results indicated that Cu2+ quenched the fluorescence intensity of human-like collagen and the quenching mechanism should belong to both dynamic and static quenching according to the Stern-Volmer equation. The binding constants and the corresponding thermodynamic parameters at different temperatures were calculated, which showed that hydrophobic interactions were the main binding force. The conclusion that Cu2+ could bind to human-like collagen was clarified by all these experimental results and theoretical data, and it could be a useful guideline for further study of human-like collagen-Cu complex.